A study on the relationship between employees organizational commitment (OC) towards organizational citizenship behavior (OCB) among employees at Petronas Carigali, Kerteh / Muhammad Firdaus Hakimi Alias - Alias, Muhammad Firdaus Hakimi (2016)
The main purpose of this study is to measuring the relationship between organizational commitment and organizational citizenship behavior and also to identify the level of three-component model (TCM) in organizational commitment with organizational citizenship behavior in Petronas Carigali, Kerteh, Terengganu. This study utilized convenience sampling techniques. The data collected by using questionnaires that required respondents to rate the suitable answers. It was measuring by using five point Likert scales. The comparisons have been used by using means. Based on my findings, the data was analyze using SPSS 20.0 and its shows that the Three Component Model of Organizational Commitment which is Affective Commitment, Continuance Commitment and Normative Commitment were analyzed in this study and it was resulted that there are relationship between Affective Commitment and Normative Commitment with Organizational Citizenship Behavior. Correlation between Organizational Commitment and Organizational Citizenship Behavior resulted to a moderate correlation. To conclude this, it was observed that Organizational Commitment can affect the Organizational Citizenship Behavior to employees in the organization. Finally, it is recommended that the research should been conduct in larger sample size.